INTEGRASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN AL-QUR’AN HADIS DI MTS. SALAFUL MUHAJIRIN, SINGKUT - Sidik, Muhtar; Sumaryati; Sofwan; Dian Permana (Jurnal Tawadhu, 2022)
Based on the author observation,it is necessary to integrate character education in learning Al-Qur’an Hadis at MTs. Salaful Muhajirin Singkut, this is because some teachers do not really understand how the process of integrating character education is. This type of research is field research, while the approach used is through a qualitative approach. The purpose of this qualitative research isto describe the phenomenon in depth, detail and thoroughness. The qualitative approach in this research in to match the empirical reality with the applicable theory by using a descriptive method. Based on the results of research conducted on the analysis of the integration of character education in learning Al-Qur’an Hadis at MTs. Salaful Muhajirin Singkut, it can be concluded that the integration of character education is carried out by planning, implementing, and assessing. In the search results, it can be seen that all character values are integrated in the lesson plan for learning Al-Qur’an Hadis at MTs. Salaful Muhajirin Singkut, then also integrated into the learning process of Al-Qur’an Hadis at MTs. Salaful Muhajirin Singkut by the subject teacher.